2016
DOI: 10.18203/issn.2454-2156.intjscirep20164306
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori infection and pre-eclampsia among pregnant women in Ardabil

Abstract: INTRODUCTIONIdentifying health priorities is an essential step in providing health education programs and changes in planning any intervention in the provision of health services and health promotion in society. One of these priorities is reducing maternal mortality. One of the major causes of mortality among pregnant women is preeclampsia, that despite extensive research, the main cause of it is unknown. Pre-eclampsia is multifactorial and many factors such as high blood pressure, obesity (BMI >30), multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The primary outcomes we focused on were preeclampsia and fetal growth restriction. Sixteen studies with a total of 10 402 women reported the influence of H pylori infection on the risk of preeclampsia. Pooled results suggested an OR of 2.51 (95% CI: 1.88‐3.34; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary outcomes we focused on were preeclampsia and fetal growth restriction. Sixteen studies with a total of 10 402 women reported the influence of H pylori infection on the risk of preeclampsia. Pooled results suggested an OR of 2.51 (95% CI: 1.88‐3.34; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…After conducting subgroup analysis on preeclampsia, fetal growth restriction, gestational diabetes mellitus, and spontaneous abortion, we found the pooled result of seven studies with a total of 4630 participants showed that CagA positivity increased the risk of preeclampsia (OR: 3.61; 95% CI: 1.61‐8.11; P = 0.002). We found that pooled cohort study results with high heterogeneity showed H pylori infection was statistically not associated with preeclampsia ( P = 0.114), fetal growth restriction ( P = 0.138), and spontaneous abortion ( P = 0.401).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were finally included in this review, which included a total number of 9787 women. Among them 879 were preeclamptic, while the remaining 8908 were recruited as healthy pregnant controls.…”
Section: Included Studiesmentioning
confidence: 99%